Utilizing Ripple Effects Mapping to Assess the Impact of an Undergraduate Global Health Program - Talia Bailes; Mia Haller; Jeanne Moseley (Ubiquity Press, 2023)
Background: In the last ten years, there has been a dramatic rise in student interest in global health as an academic discipline and an increase in academic offerings in the field at both the undergraduate and graduate levels. However, information is limited on the impact of global health programming on students, alumni, and partners involved. Objective: The objective of this study was to utilize Ripple Effects Mapping (REM) to assess the impact of an undergraduate Global Health Program on students, alumni, and international partners. Methods: REM, a new, innovative, community-centered research methodology was employed in this research study whereby three REM focus group sessions, each with 10-11 participants, were facilitated. A multi-layered textual, thematic analysis was used to analyze the data collected from REM focus group sessions. Findings: After analysis, six thematic areas emerged, each with their own underlying qualities of growth, or sub-themes, which provide insight into the manner in which the major themes contributed to student learning. Furthermore, programmatic components were identified, which aided student growth and learning. Conclusions: Findings suggest that the undergraduate Global Health Program has promoted and facilitated student growth and learning in various capacities. This study fills a gap in existing research and current knowledge by outlining the impact of an undergraduate Global Health Program on students. Additional studies should be conducted to further explore the impact of Global Health Programming on students and stakeholders.